A comprehensive chronology of the Neanderthal site Moula-Guercy, Ardèche, France. (October 2016) - Willmes, Malte; Grün, Rainer; Douka, Katerina; Michel, Véronique; Armstrong, Richard A.; Benson, Alexa; Crégut-Bonnoure, Evelyne; Desclaux, Emmanuel; Fang, Fang; Kinsley, Leslie; Saos, Thibaud; Defleur, Alban R.
Abstract: The Baume (cave) Moula-Guercy, in southeast France, contains an important sedimentary sequence, which includes the remains of a cannibalised group of Neanderthals. The chronology of the upper layers of the cave is currently constrained by a thermoluminescence date of 72 ± 12 ka, obtained from a tephra deposit (layer VI). The middle and lower layers of the cave have been constrained by biostratigraphy, pointing towards the end of MIS 5 for the Neanderthal bearing layer XV. In order to refine the chronology of the site, we applied radiocarbon, 40 Ar/ 39 Ar, U-series and ESR dating analyses. Radiocarbon dates on bone samples from layer IV showed ages older than 50 ka. 40 Ar/ 39 Ar dating on sanidines from tephra of layer VI revealed, that these volcanic minerals derived probably from the Hercynian basement, and thus provided no tangible chronological constrain. Combined CSUS/ESR results on faunal teeth place layer IV at the end of MIS 3 to MIS 4, in agreement with the radiocarbon dates and in stratigraphic order with the thermoluminescence age for layer VI. Layer VIII, with only one sample, is tentatively placed to the end of MIS 4. The age estimates for layer XIV are not conclusive, preventing an age estimation for this layer. The younger age result for layer XIV does not agree with the stratigraphy and biostratigraphy of the site and more direct dating of material from this layer is needed to resolve this discrepancy. Located just below, the crucial Neanderthal bearing layer XV is placed to the end of MIS 5 and younger than MIS 6, in agreement with the climatological and chronological deductions from the stratigraphy and biostratigraphy of the site. Direct U-series analyses on two Neanderthal teeth agree with an age for layer XV corresponding to at least MIS 5 sensu lato . The U-series results on the Neanderthal tooth 3525 show that U-mobilisation even into small teeth is highly complex, but nevertheless give an indication that this sample corresponds to MIS 5e. This is in agreement with the CSUS/ESR results from faunal teeth as well as the stratigraphy and biostratigraphy of the cave. The refined chronology corroborates the existing stratigraphic and biostratigraphic framework. Moula-Guercy layer XV, with its many human remains showing cannibalism, now stands as a reference site for this particular aspect of human behaviour. Highlights: We applied radiocarbon, 40 Ar/ 39 Ar, U-series and ESR dating analyses to Moula-Guercy. The Neanderthal bearing layer is placed to the end of MIS 5 and younger than MIS 6. U-series results show that U-mobilisation even into small teeth is highly complex. Direct U-series results on two Neanderthal teeth correspond to the end of MIS 5.